Partners at Learning: A Service-Learning Approach to Serving Public School Students from Military Families. (3rd July 2017) - Capp, Gordon; Benbenishty, Rami; Moore, Hadass; Pineda, Diana; Astor, Ron Avi; Castillo, Berenice; De Pedro, Kris T.
ABSTRACT: The majority of 4 million United States military-connected students attend public schools, and many face various challenges that stem from factors related to military service. Schools can support these students through a positive school climate and attention to their needs. University service-learning programs can enhance the experiences of military-connected students. This study presents an evaluation of the Partners at Learning program, where undergraduate university students provided tutoring to underserved students, including military-connected students. Results show that Partners at Learning tutors reported greater awareness of the unique experiences of these military-connected students, increased understanding of diverse groups, and increased interest in social justice advocacy.